Epigenetic embedding of childhood adversity: Linking adverse childhood experiences to addiction - ERK, Mehmet Aykut (Journal of Dependence, 2026)
Adverse childhood experiences shape the developing brain in ways that increase vulnerability to substance use across the lifespan. This review brings together evidence from epigenetics, neuroscience and forensic psychology to explain how early stress becomes biologically embedded. Childhood adversity alters patterns of DNA methylation in genes that regulate stress response, neuroplasticity and reward processing, including NR3C1, FKBP5, BDNF, DRD2 and OPRM1. These molecular changes heighten sensitivity to stress, weaken the capacity to experience pleasure and increase impulsive behavior. As a result, substance use often emerges as an attempt to cope with an internal environment marked by emotional and physiological dysregulation. Repeated substance use then reinforces the same biological pathways, creating a cycle that is difficult to break. Research from different countries shows a clear association between adversity, epigenetic variation and accelerated biological aging. While direct causal evidence in humans is still emerging, statistical models and animal studies suggest a potential basis for the intergenerational transmission of trauma-related susceptibility. Studies from Türkiye report strong links between childhood trauma, dissociation and substance use, although molecular research remains limited. Interpreting these findings through a forensic lens highlights the need to move beyond purely punitive views of addiction. Trauma and biologically informed approach can support more effective prevention, treatment and rehabilitation strategies.